How Rural School Mental Health Professionals Navigate the Challenges they Encounter: A Grounded Theory Analysis - Courtney J. Ober; Terry A. Wolfer; Aidyn L. Iachini (School Mental Health, 2026)
Abstract Youth mental health (MH) needs have intensified in the United States since the COVID-19 pandemic, with rural youth experiencing disproportionately high suicide rates and persistent barriers to MH care. Because schools often serve as a primary access point for identifying and addressing MH concerns, school mental health professionals (SMHPs) serve a critical role, especially in rural contexts. Unfortunately, however, many receive limited preparation for the practical realities of rural school MH (SMH) practice. This study sought to understand how SMHPs working in rural schools in one southeastern state navigate the challenges they encounter in delivering youth MH care. Secondary data collected from 15 semi-structured interviews were analyzed using a constructivist grounded theory approach. Findings highlighted four interconnected categories of navigation strategies: (1) orienting through identity and mindset, (2) building relational foundations, (3) educating oneself and others, and (4) delivering services and navigating systems. These findings position rural SMHPs as strategic navigators who legitimize and sustain their work through internal grounding, relational processes, knowledge translation, and adaptive service delivery. Implications are discussed for school and district practices that support rural SMH, graduate training and professional preparation of SMHPs, and future research on SMHP navigation strategies in rural school contexts.